Immersion education in Canada as an effective method of learning second language (Pedagogy of Higher and Secondary Education, 2014)
Ustimenko V. V. Immersion education in Canada as an effective method of learning second language.The article examines the experience of using French immersion programs in education of Canada, characteristics of such type of training are shown taking into consideration the requirements of modern Canadian society. The special attention is paid to the effectiveness of immersion education while learning second language.
Keywords: Canada; immersion education; immersion programs; multilingualism